2013
DOI: 10.1002/lt.23622
|View full text |Cite
|
Sign up to set email alerts
|

Use of rifabutin for the treatment of a latent tuberculosis infection in a patient after solid organ transplantation

Abstract: Latent tuberculosis infection is an important problem for solid organ transplant recipients because of the frequency of its occurrence and its potential for reactivation. Because of the high mortality rate associated with active tuberculosis infections in transplant recipients, guidelines from the American Thoracic Society recommend treatment for latent tuberculosis in this population. However, the choice of treatments is often difficult because liver transplant recipients may be more sensitive to isoniazid he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…A case report on the use of rifabutin for LTBI after liver transplant was recently published [26]. In this patient, the use of rifabutin resulted in adequate tacrolimus levels when the tacrolimus dose was increased 2.5-fold.…”
Section: Latent Tuberculosis: Treatment Challenges In Solid Organ Tramentioning
confidence: 92%
“…A case report on the use of rifabutin for LTBI after liver transplant was recently published [26]. In this patient, the use of rifabutin resulted in adequate tacrolimus levels when the tacrolimus dose was increased 2.5-fold.…”
Section: Latent Tuberculosis: Treatment Challenges In Solid Organ Tramentioning
confidence: 92%
“…Although rifabutin is not recommended as first line therapy for latent TB infection (LTBI), it has been used in liver transplant patients, who have experience isoniazid‐induced hepatoxicity and to optimize maintenance of calcineurin inhibitor levels . One pilot study (n = 44) for treatment of LTBI in people living with HIV, showed favourable ADR and completion rates comparing three months bi‐weekly rifabutin in combination with isoniazid compared with six months daily isoniazid .…”
Section: Toxicity and Switch Optionmentioning
confidence: 99%
“…Bacterial translocation caused by intestinal barrier dysfunction is the main source of E coli (1,9,10). Many bacterial toxins and inflammatory mediators are absorbed into the bloodstream, increasing multiple-organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%